Temporal Tissue Remodeling in Volumetric Muscle Injury with Endothelial Cell-Laden Patterned Nanofibrillar Constructs - Krista M. Habing; Cynthia A. Alcazar; Nathaniel Dobson; Yong How Tan; Ngan F. Huang; Karina H. Nakayama (Bioengineering)
A primary challenge following severe musculoskeletal trauma is incomplete muscle regeneration. Current therapies often fail to heal damaged muscle due to dysregulated healing programs and insufficient revascularization early in the repair process. There is a limited understanding of the temporal changes that occur during the early stages of muscle remodeling in response to engineered therapies. Previous work demonstrated that nanotopographically patterned scaffolds provide cytoskeletal guidance and direct endothelial angiogenic and anti-inflammatory phenotypes. The aim of this study was to evaluate how endothelial cell (EC) patterning guides temporal and histomorphological muscle remodeling after muscle injury. In the current study, mice were treated with EC-laden engineered constructs that exhibited either aligned or random patterning of collagen nanofibrils, following a volumetric muscle loss injury (VML). Remodeling was evaluated at 2, 7, and 21 days post injury. Over the 21-day study, all groups (Acellular Aligned, EC Aligned, EC Random) demonstrated similar significant increases in vascular density and myogenesis. Animals treated with acellular controls demonstrated a two-fold decrease in muscle cross-sectional area between days 2 and 21 post injury, consistent with VML-induced muscle atrophy; however, animals treated with patterned EC-laden constructs exhibited preservation of muscle mass. The implantation of an EC-laden construct led to a 50% increase in the number of animals exhibiting areas of fibrous remodeling adjacent to the construct, along with greater collagen deposition (p < 0.01) compared to acellular controls 21 days post injury. These findings suggest that nanotopographically patterned EC-laden constructs may guide early muscle-protective programs that support muscle mass retention through myo-vascular independent pathways.